Administrative Law in Europe: Between Common Principles and National Traditions - Ruffert, Matthias (Europa Law Publishing, 2013)
Administrative Law in Europe: Between Common Principles and National Traditions. Edited by Matthias Ruffert. European Administrative Law Series (7); Acknowledgements; Contents; About the Authors; Chapter 1. Administrative Law in Europe: Between Common Principles and National Traditions by Eberhard Schmidt-Aßmann; Chapter 2. Tradition in English Administrative Law by Andrew Le Sueur; Chapter 3. National Traditions in French Administrative Law by Pascale Gonod; Chapter 4. German Traditions in Administrative Law. Obstacles to a Common Legal Framework? by Jens-Peter Schneider
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift -- 2012 -- Dornburg; Verwaltungsrecht; Europäische Union